Intraspecific and interspecific trait variability in tadpole meta-communities from the Brazilian Atlantic rainforest - Xavier Jordani, Mainara [UNESP]; Mouquet, Nicolas; Casatti, Lilian [UNESP]; Menin, Marcelo; de Cerqueira Rossa-Feres, Denise [UNESP]; Albert, Cécile Hélène (Wiley, 2019)
A better understanding of species coexistence and community dynamics may benefit from more insights on trait variability at the individual and species levels. Tadpole assemblages offer an excellent system to understand the relative influence of intraspecific and interspecific variability on community assembly, due to their high phenotypic plasticity, and the strong influence that environmental variables have on their spatial distribution and individual performance. Here, we quantified the intraspecific and interspecific components of tadpoles’ trait variability in order to investigate their relative role in shaping tadpole communities. We selected eight functional traits related to microhabitat use, foraging strategies, and swimming ability. We measured these traits on 678 individuals from 22 species captured in 43 ponds in the Atlantic Forest. We used single- and multitrait analyses to decompose trait variability. To explore the action of external and internal filtering on community assembly, we used a variance decomposition approach that compares phenotypic variability at the individual, population, community and regional levels. On average, 33% of trait variability was due to within-species variation. This decomposition varied widely among traits. We found only a reduced effect of external filtering (low variation in the height of the ventral fin within ponds in comparison to the total variation), whereas the internal filtering was stronger than expected. Traits related to the use of different microhabitats through the water column were generally less variable than traits related to swimming ability to escape of predators, with tail traits being highly variable within species. Our study highlights the importance of incorporating both intraspecific and interspecific, trait differences and of focusing on a diversity of traits related to both stabilizing niche and fitness differences in order to better understand how trait variation relates to species coexistence.
Keywords: community assembly; ecological niche; fitness differences; phenotypic variability; stabilizing niche differences